Diagnostic significance of urinary thiodiglycolic acid as a possible tool for studying the role of vitamins B12 and folates in the metabolism of thiolic substances - Navrátil, Tomáš; Petr, Miroslav; Šenholdová, Zdeňka; Přistoupilová, Kamila; Přistoupil, Tomáš Ivan; Heyrovský, Michael; Pelclová, Daniela; Kohlíková, Eva (Physiological research, 2007)
We have found that the determination of thiodiglycolic acid (TDGA) in urine may help to characterize metabolic imbalance of substances participating in methionine synthesis, which leads to hyperhomocystinuria. From the metabolic scheme, based on a proper combination of known facts, we attempted to theoretically explain and to demonstrate the possibilities of TDGA formation via different ways of homocysteine transformation. This scheme was used in evaluating the results obtained by testing urine of a woman suffering from impaired function of methionine synthase reductase (CblE type of homocystinuria). The amount of TDGA excreted in her morning urine was very sensitive to the changes in her treatment based upon a combination of N5-formyl tetrahydrofolate, betaine and vitamin B12. Vitamin B12 given in the evening either alone or together with betaine increased the TDGA excretion in the morning urine up to ten times. On the other hand, in the absence of vitamin B12, betaine in combination with N5-formyl tetrahydrofolate hindered the appearance of TDGA in the morning urine. Generally, the determination of TDGA in urine of an appropriately pretreated patient may indicate the degree of success of the treatment.
Keywords: Thioglycolates; betain; Betaine; lidé; Financing, Government; formyltetrahydrofoláty; financování vládou; thioglykoláty; homocystein; Homocysteine; vitamin B 12; polarografie; Vitamin B 12; Humans; Polarography; Formyltetrahydrofolates